Relationship between Perceived Supervisor Support (PSS) and Organizational Commitment (OC) among academicians in UiTM Malacca / Nani Shuhada Sehat, Siti Rohana Daud and Mazida Ismail - Sehat, Nani Shuhada; Daud, Siti Rohana; Ismail, Mazida (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
Academicians play a vital role in a learning institution, therefore in order to maintain the number of academicians, the support of the supervisor is very crucial to maintain the commitment of academicians especially in higher learning institution. The purpose of this study is to examine the relationship between perceived supervisor support (PSS) and organizational commitment (OC) and to determine which types of organizational commitment namely affective commitment (AFFOC), normative commitment (NORMOC) and continuance commitment (CONTOC) was most influenced by PSS among academicians in UiTM Malacca. The questionnaires were distributed randomly to 200 academicians in UiTM Malacca but only 119 were returnable, completed and useful. Data from 119 academicians were analyzed using Statistical Package for Social Science (SPSS). The Pearson Correlation test was used to test the relationship between PSS and all three OC. A regression analysis was used to determine which type of the three OC was most influenced by PSS among academicians in UiTM Malacca. All variables are proven reliable after going through reliability test. The findings suggest that PSS has positive relationship with AFFOC, CONTOC and NORMOC but only AFFOC and NORMOC have significant relationship with PSS. Meanwhile, all the three OC were influenced by PSS among respondents in UiTM Malacca. It concludes that organizational commitment of all of the academicians in UiTM Malacca is very much dependent in perceived supervisor support that they receive.